1993
DOI: 10.1128/mcb.13.5.2909
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 70 is altered by age and diet at the level of transcription.

Abstract: Because heat shock proteins have been shown to play a critical role in protecting cells from hyperthermia and other types of physiological stresses, it was of interest to determine what effect age and caloric restriction have on the ability of cells to regulate the expression of heat shock protein 70 (hsp70), the most prominent and most evolutionarily conserved of the heat shock proteins. Caloric restriction is the only experimental manipulation known to retard aging and increase survival of mammals. The abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
2
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(115 citation statements)
references
References 36 publications
5
105
2
3
Order By: Relevance
“…The novel feature of this study is that after heat shock, both fast and slow skeletal muscles from aged animals demonstrated similar HSF activation and Hsp72 accumulation as the same muscles from adult animals. These results may appear to contrast with those of previous studies (Liu et al 1989;Choi et al 1990;Fargnoli et al 1990;Blake et al 1991;Heydari et al 1993;Nitta et al 1994;Kregal et al 1995), but a number of factors may explain these apparent differences. First, most studies that have examined the heat shock response and aging have used cultured cells or cells removed from aged animal tissues (Liu et al 1989;Choi et al 1990;Fargnoli et al 1990;Heydari et al 1993), but the in vivo heat shock response has been reported to lack the coordinated control that is characteristic of cultured cell populations (Blake et al 1990;Locke and Tanguay 1996a).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The novel feature of this study is that after heat shock, both fast and slow skeletal muscles from aged animals demonstrated similar HSF activation and Hsp72 accumulation as the same muscles from adult animals. These results may appear to contrast with those of previous studies (Liu et al 1989;Choi et al 1990;Fargnoli et al 1990;Blake et al 1991;Heydari et al 1993;Nitta et al 1994;Kregal et al 1995), but a number of factors may explain these apparent differences. First, most studies that have examined the heat shock response and aging have used cultured cells or cells removed from aged animal tissues (Liu et al 1989;Choi et al 1990;Fargnoli et al 1990;Heydari et al 1993), but the in vivo heat shock response has been reported to lack the coordinated control that is characteristic of cultured cell populations (Blake et al 1990;Locke and Tanguay 1996a).…”
Section: Discussioncontrasting
confidence: 94%
“…Cells and tissues from aged animals have been reported to exhibit decreased Hsp induction and expression after heat shock (Liu et al 1989;Choi et al 1990;Fargnoli et al 1990;Blake et al 1991;Heydari et al 1993;Nitta et al 1994;Kregal et al 1995;Locke and Tanguay 1996b). The diminished ability to induce Hsps in aged cells and tissues appears to result from decreased HSF activation (Heydari et al 1993;Locke et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging usually lowers the expression of antioxidant enzymes and stress protein expression. This loss can be modulated through interventions with diet or exercise [58,62,118]. One effect of the combined treatment EA was a significant increase in the expression of inducible heme oxygenase (HO-1) also known as HSP32.…”
Section: Discussionmentioning
confidence: 99%
“…Heydari et al have shown that the half-life of mRNA for HSP70 was longer in hepatocytes isolated from old rats than that of HSP70 mRNA in hepatocytes isolated from young adult rats. 15 ) Thus, it seems likely that HSP70 is degraded more slowly with increasing age.…”
Section: Discussionmentioning
confidence: 99%